FROM DISINFORMATION TO GEORIVALIZATION: THE RUSSIAN INFORMATION WAR AGAINST POLAND IN THE CONTEXT OF CRITICAL GEOPOLITICS - Piotr (Torun International Studies, 2025)
This article aims to analyze the main axes of Russian disinformation directed at Poland within the framework of critical geopolitics, especially in the context of the war in Ukraine. The justification for this study lies in the increasing prevalence of Russian disinformation in Polish scientific literature and its impact on international security. The methodology involves critical discourse analysis and thick description of content from Russian press and news agencies, focusing on primary sources. The timeframe for the analysis covers the period immediately preceding and three months following the outbreak of the war in Ukraine in 2022. The findings identify four key disinformation narratives: a) Polish imperialism; b) Polish-Ukrainian relations; c) preparations for war; d) liquidation of Poland. This research contributes to the literature by providing an empirical case study demonstrating the applicability of critical geopolitics to understanding contemporary information warfare. The conclusions and implications suggest that Russian disinformation seeks to manipulate perceptions, sow discord, and justify its geopolitical actions by constructing a negative image of Poland.